Design of Culinary Tourism and Shopping Center in Tongging Village (Green Architecture) - Hemanda, Endang Putri; Ginting, Nurlisa (Talenta Publisher, 2020)
Nowadays, eating and drinking is not only a basic need but also has become one of the tourist destinations. Tongging Village is one of the tourist villages with views of Lake Toba and its grilled fish that has the potential to develop culinary and shopping tourism. Besides, Tongging Village is also directed by the Indonesian Ministry of Tourism to become a culinary tourism and shopping center on Lake Toba. In designing a culinary tourism center and shopping, the application of green architecture is the right choice by utilizing natural resources and not damaging existing natural conditions. The design method was carried out qualitatively by a sequential systematic process and taking data through field surveys and interviews with the headman and local communities so that it produces points that could be used in designing. The design of culinary tourism and shopping centers with the application of green architecture aims to utilize natural resources without damaging natural conditions and attract tourist enthusiasm so that culinary and shopping tourism centers become one of the main tourist destinations for the Lake Toba Region which will affect the income of Indonesia's creative economy. Keywords: Tourism, Tongging, Culinary Tourism, Shopping, Green Architecture